Arthroscopic anatomical reconstruction of anterior talofibular ligament and calcaneofibular ligament for chronic ankle instability - Yunfeng Zhou MD; Bin Song MD (Foot & Ankle Orthopaedics, 2018)
Category: Arthroscopy Introduction/Purpose: To evaluate the clinical results of an anatomical reconstruction of anterior talofibular ligament and calcaneofibular ligament under arthroscopy in treatment of chronic ankle instability. Methods From June 2013 to August 2016, 27 patients (28 ankles) with chronic ankle instability were treated with the anatomical reconstruction of anterior talofibular ligaments and calcaneofibular ligaments. All patients were evaluated preoperatively and at the last follow up using the visual analog scale(VAS) score, American Orthopaedic Foot and Ankle Society (AOFAS) score. The talar tilt angle and anterior translation were assessed radiographically in pre- and postoperative ankle stress views. Methods: From June 2013 to August 2016, 27 patients (28 ankles) with chronic ankle instability were treated with the anatomical reconstruction of anterior talofibular ligaments and calcaneofibular ligaments. All patients were evaluated preoperatively and at the last follow up using the visual analog scale(VAS) score, American Orthopaedic Foot and Ankle Society (AOFAS) score. The talar tilt angle and anterior translation were assessed radiographically in pre- and postoperative ankle stress views. Results: The operations were lasted for 75.8 minutes(72~104 minutes). 28 cases were received a mean follow up of 14.8 months(range, 12~25 months. The mean VAS pain score decreased from 5.79 to 1.54(t=26.63, P<0.01), and the medial AOFAS score improved from 63.64 to 90.21(t=-16.57, P<0.01). Imageological examination were completed 16.8 months after the operation (range, 12~25 months). The mean talar tilt decreased from 15.6°to 6.01°(t=25.39, P<0.01),and anterior translation of the talar reduced from a mean of 10.82 to 4.03 mm(t=15.79, P<0.01). Conclusion: Arthroscopic anatomical reconstruction of anterior talofibular ligament and calcaneofibular ligament could improve the function and stability of ankle joints effectively, providing a valid option for treating chronic ankle instability.